Road to School Transformation 2025: A Systematic Literature Review on Teacher Autonomy in Malaysia - Isa, Anniliza Mohd; Mydin, Abdul Ghani Kanesan Abdullah Al-Amin (Human Resource Management Academic Research Society, 2021)
Teacher autonomy in Malaysia is gaining attention among policy makers, making it a key element in School Transformation Programs (SLP25). However, research on teacher autonomy in Malaysia is still scarce and have minimal interest among social science researchers compared to other countries. The purpose of this study was to collect and analyse previous studies on teacher autonomy in Malaysia. The objective of this study was to investigate the extent, issues, and challenges of teacher autonomy in Malaysia. There were three research questions in this review, (1) How was teacher autonomy level in Malaysia? (2) What type of teacher autonomy implemented in Malaysia? and (3) What are the issues and challenges faced by Malaysian teachers regarding teacher autonomy? To address the research questions, a systematic literature review was performed using four-phase in Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). Findings show that despite excercising guided autonomy, teachers in Malaysia show an encouraging level of autonomy. Overall, the main challenges related to teacher autonomy are teachers’ attitudes and behaviours toward given autonomy